Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1118/1.4908226
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and normalization of triple coincidences in PET

Abstract: Purpose: Triple coincidences in positron emission tomography (PET) are events in which three γ-rays are detected simultaneously. These events, though potentially useful for enhancing the sensitivity of PET scanners, are discarded or processed without special consideration in current systems, because there is not a clear criterion for assigning them to a unique line-of-response (LOR). Methods proposed for recovering such events usually rely on the use of highly specialized detection systems, hampering general a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…These events are the same as the random coincidence events in a conventional PET and can be corrected using the delayed coincidence method. Thus, in our system, only energy discrimination is used to distinguish prompt and annihilation γ ‐rays, although another method could distinguish between them based on the collinearity of annihilation photons …”
Section: Methodsmentioning
confidence: 99%
“…These events are the same as the random coincidence events in a conventional PET and can be corrected using the delayed coincidence method. Thus, in our system, only energy discrimination is used to distinguish prompt and annihilation γ ‐rays, although another method could distinguish between them based on the collinearity of annihilation photons …”
Section: Methodsmentioning
confidence: 99%
“…The NN scheme further requires calculations in a network trained by simulation data. However, it is reported that the computational burden of the NN scheme is manageable, even in existing PET systems …”
Section: Discussionmentioning
confidence: 99%
“…First, we tested different energy criteria for triple coincidence for IDS validation because they are likely to determine the number of IDS events to be recovered. Second, we compared different recovery schemes that are expected to be efficient for small ‐ animal PET geometry and relatively simple for real implementation . An accurate recovery scheme has to be applied to correctly find the true LORs of the IDS events .…”
Section: Introductionmentioning
confidence: 99%
“…A recent proposal is to use what has been termed the triple coincidence, which works with any third photon because it can be distinguished from random or scatter; therefore, the triple coincidences can be included in iterative reconstruction models (96). Events coming from triple-photon isotopes can be detected separately from pure positron emitters using precalculated double-coincidence probabilities that are used to assign the triple event to one of the possible LORs.…”
Section: Application Developmentsmentioning
confidence: 99%